POLITICAL DYNAMICS OF THE 2024 NORTH SUMATRA GUBERNATORIAL ELECTION: IMPLICATIONS AND CHALLENGES - Batara Harahap (SOSIOEDUKASI, 2026)
This study analyzes the political dynamics of the 2024 North Sumatra gubernatorial election (Pilgub Sumut), exploring its implications and challenges as a reflection of local democracy amidst identity politics (Batak, Malay, Javanese ethnicities), social polarization, and digital media disruption. Methodology: Employing a qualitative case study approach, data were collected through in-depth interviews with political actors and observers, field observations, and document analysis from KPU and Bawaslu. Data validity was ensured through source triangulation. Findings reveal five key insights: (1) the dominance of pragmatic coalitions based on candidate electability, (2) the instrumentalization of identity politics as a mobilization strategy with the risk of social fragmentation, (3) the dual role of social media—effective in engaging youth voters yet vulnerable to disinformation, (4) persistent structural challenges such as money politics, and (5) a shift in voter behavior towards rational considerations based on candidate track records. Conclusion: The 2024 election illustrates the dilemma of electoral democracy where identity-based tactics and pragmatic interests marginalize substantive issues (e.g., Lake Toba deforestation, gender inequality). The study underscores the need for strengthening digital literacy, enforcing anti-transactional politics laws, and promoting inclusive policy-based reconciliation to transform identity politics into policy accountability.